Pengaruh Penerapan Anggaran Berbasis Kinerja Terhadap Akuntabilitas Kinerja Instansi Pemerintah (Studi Pada Satuan Kerja Perangkat Daerah Kota Bandung) - Ferina Anggraeni; Suji Abdullah Saleh (Indonesian Accounting Research Journal, 2020)
The budget function as an instrument of public accountability for the management of public funds. To support this, the government needs a good approach in order to achieve predetermined goals. Performance-based budgets are used by the government as a reference in preparing budgets to achieve performance goals and targets and to meet performance accountability. This study aims to determine how the implementation of performance-based budgeting and performance accountability of government agencies in Bandung City Regional Work Units, as well as to analysis the effect of implementing performance-based budgets on the performance accountability of government agencies. The research method used in this research is quantitative. The sampling technique used purposive sampling. The sample was selected based on certain criteria, namely 26 SKPDs with the status of regional offices and regional agencies in Bandung City. Data collection was carried out by distributing questionnaires to the planning or budgeting sector and the field of finance or accounting, the number of respondents in this study was 70 people. The method of analysis in this study uses simple linear regression analysis with the help of SPSS 24 Software. The results show that the implementation of performance-based budgets has a positive and significant effect on the accountability of the performance of government agencies.